OVERVIEW OF UNDERSTANDING AND PREPAREDNESS FOR EARTHQUAKES IN THE PERSPECTIVE OF VOCATIONAL HIGH SCHOOL STUDENTS - Yuwita Novyanti; Henita Rahmayanti; Irika Widiasanti (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
Knowledge of disaster mitigation is the most essential component and a key factor for preparedness. The possessed knowledge typically influences attitudes and concerns, fostering readiness to anticipate disasters. Vocational High School students should be informed about the various disasters that frequently occur in their areas, as well as the procedures to face sudden disasters. The significant loss of lives and various damages to buildings and facilities in the vicinity underscore the need for a deeper examination of mitigation efforts. The objective of this study is to assess the level of understanding and preparedness of Vocational High School students regarding earthquake natural disasters. The research method employed is quantitative, with descriptive statistics as the analytical technique. The instruments used include test instruments and non-test instruments utilizing Google Forms to collect data from several Vocational High Schools in various cities in DKI Jakarta, Sukabumi, and Tangerang. The research findings reveal that 42% of students are unaware of earthquake disaster mitigation measures. Additionally, 69% of students lack knowledge about minimizing damage from earthquakes in terms of building construction. Furthermore, 65% of students are unfamiliar with images related to earthquake-resistant construction. Moreover, 52% of students still do not know the local earthquake resilience features of earthquake-resistant houses. Lastly, 52% exhibit a panicky attitude, hastily evacuating buildings during an earthquake. The conclusion drawn from this research is that the knowledge of Vocational High School students regarding earthquake disasters and their mitigation measures is still low.